(untitled) (Journal of human and social sciences, 2022)
structuralism in various scientific fields, clarifying its conceptual foundation as a methodology concerned with the “structure” or internal relations of elements within a whole. Using historical, descriptive, analytical, and comparative approaches, the study seeks to answer key questions: What is the relationship between structuralism and other philosophies? How did it emerge from the philosophical debates of its time? To what extent does it align or differ from preceding currents? And can it be applied as a methodology across different sciences? The importance of the study lies in uncovering the philosophical underpinnings of structuralism, demonstrating its influence on knowledge production, and clarifying its role as a theoretical and methodological framework that connects diverse fields of inquiry.